The perceptual experience of the school space through artistic practice - Kumm, Rosely (Revista do Colóquio, 2023)
The landscape, for Brazilian geographer Milton Santos, is everything that the eye can see, not just the shapes, but also the colors, smells and sounds provided by the experience of inhabiting a place. Since it is “everything that the eye can see”, its construction depends directly on the observer’s perception, making it possible to select artistic productions from different categories as constituent elements of this landscape. This experience report is part of a study on the landscape of everyday school life and how multiple artistic proposals can change and give new meaning to it. By taking this study to the educational environment, we intend to investigate the child’s perceptions in relation to the everyday landscape, developing critical sense, and highlighting their role as protagonists in this environment.